Hydrodynamic characteristics of marine composite propeller blade using a numerical approach - Manikant Paswan; Kapil Kumar; M. L. P. Kishore; Vijay K. Singh; R. K. Behra; Chandra S. Saran (Institute of Advanced Engineering and Science, 2021)
The aim of the present research work is to investigate the hydrodynamic characteristics (pressure distribution, rotational speed, thrust, and torque) of the conventional B-series composite propeller blade. The open water efficiency for the scaled model of the composite propeller blade is computed using computational fluid dynamics (CFD) fluent simulation tool. The obtained numerical results show that the propeller will operate at optimum efficiency for the given speed condition and perform with reduced efficiency at other operational speeds. The computed responses are also validated with the standard B-series data which verifies the accuracy and robustness of the present numerical approach in analyzing the performance characteristics of propellers. The deviation in solution ranges from 5 to 15% in the case of thrust, and 10 to 20% in the case of torque. Pressure estimation is usually quite accurate with a 5 to 8% variation. The tabular data of pressure distribution over the propeller blade may be used for further structural analysis.